THE INFLUENCE OF MOTIVATION, SELF-EFFICACY AND FAMILY ENVIRONMENT TO INTEREST TO BECOME A TEACHER - Putri, Azrah Maysa; Wolor, Christian Wiradendi; Swaramarinda, Darma Rika (Sindoro: Cendikia Pendidikan, 2024)
This study aims to identify the influence of motivation, self-efficacy and family environment to interest to become a teacher. This study applied a quantitative approach with a data collection method in the form of a survey with a questionnaire as the research instrument. The population in this study are the Economics and Administration Education Students of, Faculty of Economic and Business, Universitas Negeri Jakarta year 2022. The analysis techniques used in this study are statistical descriptive analysis, multiple linear regression, the classical assumption test, and hypothesis testing analysis. The results of this research shows that: 1) motivation does not affect interest in becoming a teacher, 2) self-efficacy also does not affect interest in becoming a teacher, 3) family environment does affect interest in becoming a teacher by 29.30% and 4) motivation, self-efficacy, and family environment together influence interest in becoming a teacher by 7.10%. The results of this study is expected to contribute to developing knowledge about education, especially for researchers who are interested in analyzing the influence of motivation, self-efficacy, and family environment to interest in becoming a teacher.